Students' Perceptions Toward Using Flash Cards in EFL Classrooms - Ahmad F. Idris; Siska Yuliawati; Najwa Riskiyani; Naf’an Tarihoran (MO.RI Publishing, 2026)
Vocabulary acquisition remains one of the most persistent challenges faced by students learning English as a Foreign Language, particularly in the Indonesian educational context, where learners have limited exposure to authentic English use in daily life. Flash cards, as a form of visual learning media that integrates written words with images, have been recognized as a practical and effective tool for supporting vocabulary instruction and strengthening long-term word retention in EFL classrooms. This study investigates students’ perceptions of the use of flashcards in EFL classrooms at the university level, with a specific focus on a higher education EFL context in Banten, Indonesia — a population and setting underrepresented in the existing literature. Unlike prior studies that examined remote or primary-school settings, this study targets university-level EFL learners and examines a broader range of perception dimensions including motivation, comprehension, retention, ease of use, and speaking ability. Employing a descriptive quantitative research design, data were collected through a validated structured questionnaire (Cronbach’s ? = .87) distributed via Google Forms to 100 EFL students with verified experience in flashcard-based vocabulary learning activities. Purposive sampling was applied based on measurable criteria of prior flashcard exposure. The collected responses were analyzed descriptively through frequency, percentage, mean, and standard deviation distributions. The findings reveal that students hold predominantly positive perceptions of flash cards, perceiving the medium as instrumental in increasing their motivation to learn new vocabulary, facilitating comprehension of word meanings through visual support, and strengthening vocabulary retention over time. The illustrations embedded in flashcards were widely acknowledged as helpful in associating words with concrete meanings, thereby reducing the cognitive load of learning unfamiliar vocabulary. Although students showed a comparatively moderate response to the direct impact of flash cards on speaking proficiency, the overall responses confirm that flash cards serve not only as an effective vocabulary-learning tool but also as a motivating medium that fosters active student engagement and creates a more interactive classroom atmosphere. These findings offer practical implications for EFL teachers in selecting and applying student-centered instructional media to enrich vocabulary teaching and improve learning outcomes.